Credit Policy of Polish Banks during The COVID-19 Pandemic - WÓJCIK-MAZUR Agnieszka (Communications of International Proceedings, 2021)
The lending activity of banks is determined by the conditions of the macro-environment and is dependent on the cyclical position of the economy and the limitation of credit supply by banks. In crisis situations, banks tighten lending policies, leading to a deeper recession and a further reduction in GDP. On the one hand, this may be dictated by the economic condition of banks themselves and, on the other, by their tendency to be overly cautious in assessing creditworthiness during a recession. Consequently, they limit the financing of even effective economic projects carried out by entities not so strongly affected by the crisis phase. Therefore, the aim of the paper is to present the preliminary assessment of the credit policy of the two largest Polish banks: PKO BP SA and PKO SA in the pandemic period, i.e. the year 2020. The analysis shows that banks introduced in 2020 various facilities and debt moratoria for SME, corporate and household customers, both bank and statutory. The analysis showed that as a result of the deteriorating economic situation resulting from the COVID-19 pandemic, banks in 3 and 4Q2020 reduced the restrictiveness of loan granting criteria, which did not stop a slight reduction in bank lending activity in the fourth quarter of 2020. However, this situation may change substantially in 2021 due to the continuing pandemic and the local burden on the Polish banking sector, including in particular the franc-loan problems of Polish banks.
Keywords: Credit Policy; Bank; Pandemic